Digital Maturity Level Measurement and Strategic Improvement Maturity Level at PT.XYZ (International Journal of Scientific Research and Management (IJSRM), 2025)
In the era of dynamic and rapidly evolving digital landscape, industries are undergoing disruptive transformations driven by the adoption of advanced technologies such as Clouds System, Internet of Things (IoT), and Automation. These digital tools are increasingly utilized to enhance system integration, operational efficiency, and cost-effectiveness. This research investigates the digital transformation journey of PT. XYZ, a company engaged in the growing, processing, and global distribution of unmanufactured tobacco (semi-processed). In pursuit of digital competitive advantage, PT. XYZ has implemented various digital tools and system, including adopting Enterprise Resource Planning (ERP) system, weather sensors, smart treatment systems, and digital applications across multiple departments. The objectives of this study are: first, to measure the level of digital maturity at PT. XYZ applying the Forrester Digital Maturity Model 4.0, which encompasses four main dimensions—Culture, Technology, Organization, and Insights—across 28 indicators. Second, to provide recommendations for enhancing digital maturity using the Digital Strategy Development framework from the MIT Sloan Management Review initiative in collaboration with Deloitte University Press to guide PT. XYZ in improving its digital maturity. This study is a qualitative research methodology using questionnaires and interviews involving a total of 42 respondents and interviewees from leadership roles, including Supervisors, Heads, Managers, and Executive Management. The analysis results indicate that PT. XYZ is at Maturity Level 3 – Collaborators in its digital transformation journey, meaning PT. XYZ has the capability to adopt and implement cloud-based systems, digital technologies in their operations, and has leaders with digital leadership competencies. To advance to Maturity Level 4 – Differentiators, several strategies can be implemented by PT. XYZ, such as enhancing employee (staff) digital competencies, developing measurement and evaluation tools for digital projects, and improving collaboration and understanding of internal and external digital strategies.